2019
DOI: 10.1186/s12879-019-4029-9
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-impregnated dressing for the prophylaxis of central venous catheter-related complications: a systematic review and meta-analysis

Abstract: Background Several randomized controlled trials (RCTs) evaluated the role of Chlorhexidine-impregnated dressing for prophylaxis of central venous catheter (CVC) related complications, but the results remained inconsistent, updated meta-analyses on this issue are warranted. Methods A meta-analysis on the RCTs comparing Chlorhexidine-impregnated dressing versus other dressing or no dressing for prophylaxis of central venous catheter-related complications was performed. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 41 publications
0
51
0
7
Order By: Relevance
“…CHX-impregnated dressings were tested in cancer and ICU patients in randomized trials showing a reduction in CRI rates compared with standard dressings, and this finding could be confirmed in a recent systematic review and meta-analysis [31, [144][145][146][147][148]. A recent multicenter randomized trial studied the use of dressings containing CHX-containing gel pads compared with standard non-impregnated dressings in 613 neutropenic cancer patients using the stringent definition of definite CRBSI and probable CRBSI [10,31].…”
Section: Cvc Site Dressing and Anti-infective Capsmentioning
confidence: 94%
“…CHX-impregnated dressings were tested in cancer and ICU patients in randomized trials showing a reduction in CRI rates compared with standard dressings, and this finding could be confirmed in a recent systematic review and meta-analysis [31, [144][145][146][147][148]. A recent multicenter randomized trial studied the use of dressings containing CHX-containing gel pads compared with standard non-impregnated dressings in 613 neutropenic cancer patients using the stringent definition of definite CRBSI and probable CRBSI [10,31].…”
Section: Cvc Site Dressing and Anti-infective Capsmentioning
confidence: 94%
“…A recent meta-analysis showed that chlorhexidine-impregnated dressings reduced catheter-related bloodstream infections [ 9 ]. To our knowledge, a direct comparison between gel-dress and sponge-dress has never been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several prevention measures are well known in the literature [3][4][5][6][7]. Among them, chlorhexidine-impregnated dressings were beneficial in various studies to prevent catheter-related bloodstream infections [8,9] and were currently recommended by the Centers for Disease Control and Prevention (CDC) [10]. Two types of chlorhexidine-impregnated dressing are currently used: chlorhexidine-impregnated sponges (spongedress) [11] and chlorhexidine gel dressing (gel-dress) [12].…”
Section: Introductionmentioning
confidence: 99%
“…A maioria dos achados da literatura em relação ao CGCHX tratam da sua capacidade de redução de infecção de corrente sanguínea relacionada ao cateter ou redução de colonização do CVC 4,9,10,[13][14][15][16][17][18][19][20] .…”
Section: Discussionunclassified
“…Dois estudos recentes 13,16,20 demonstraram que os curativos impregnados com clorexidina reduzem as taxas de infecção relacionada ao cateter ou o risco de colonização de cateter venoso central, porém com algumas ressalvas.…”
Section: Discussionunclassified